Synergy of retinoic acid and BH3 mimetics in MYC(N)-driven embryonal nervous system tumours - Seiboldt, Till; Zeiser, Constantia; Nguyen, Duy; Çelikyürekli, Simay; Herter, Sonja; Najafi, Sara; Stroh-Dege, Alexandra; Meulenbroeks, Chris; Mack, Norman; Salem-Altintas, Rabia; Westermann, Frank; Schlesner, Matthias; et al. (British journal of cancer, 2024)
Certain paediatric nervous system malignancies have dismal prognoses. Retinoic acid (RA) is used in neuroblastoma treatment, and preclinical data indicate potential benefit in selected paediatric brain tumour entities. However, limited single-agent efficacy necessitates combination treatment approaches.
Gesehen am 22.01.2025